Stafne bone defect: a report of two cases and diagnostic considerations - Mafra, Rodrigo Porpino; Vasconcelos, Marcelo Gadelha; Vasconcelos, Rodrigo Gadelha; Lima, Emeline das Neves de Araújo; Iglesias, Déborah Pitta Paraíso; Queiroz, Lélia Maria Guedes (Brazilian Dental Science, 2017)
Stafne bone defects are asymptomatic lingual bone depressions of the lower jaw, frequently caused by soft tissue inclusion. The common variant of this entity affects the third molar region, below mandibular canal, and is mostly diagnosed incidentally during routine radiographic examination. The uncommon anterior variant is relatively rare and located in the premolar region of the mandible. Sublingual salivary glands are thought to be responsible for the development of this variant. The aim of this report was to describe a case of Stafne bone defect in the anterior region of mandible and a case in posterior mandible, with emphasis on clinical and radiographic findings. Dental clinicians should be aware of this entity, aiming to avoid unnecessary biopsies. In most cases, clinical and radiographic follow-up is the recommended conduct.